2018
DOI: 10.1161/jaha.118.009507
|View full text |Cite
|
Sign up to set email alerts
|

Prior Direct Oral Anticoagulant Therapy is Related to Small Infarct Volume and No Major Artery Occlusion in Patients With Stroke and Non‐Valvular Atrial Fibrillation

Abstract: BackgroundThe aims of the present study were to investigate the relationships between prior direct oral anticoagulant (DOAC) therapy and infarct volume and the site of arterial occlusion in patients with acute ischemic stroke and non‐valvular atrial fibrillation.Methods and ResultsFrom March 2011 through November 2016, consecutive patients with acute ischemic stroke in the middle cerebral artery territory and non‐valvular atrial fibrillation were recruited. The infarct volume was assessed semi‐automatically us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
1
14
0
2
Order By: Relevance
“…Sakamoto et al found DOAC therapy to be associated with smaller infarct sizes on MRI in a smaller study (40 non-therapeutic VKA, 22 confirmed therapeutic VKA and 29 DOAC, 239 controls) [9]. However, the authors compared non-therapeutic VKA and DOAC treatment with controls without laboratory assessment of DOAC activity or information on compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sakamoto et al found DOAC therapy to be associated with smaller infarct sizes on MRI in a smaller study (40 non-therapeutic VKA, 22 confirmed therapeutic VKA and 29 DOAC, 239 controls) [9]. However, the authors compared non-therapeutic VKA and DOAC treatment with controls without laboratory assessment of DOAC activity or information on compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, data on imaging characteristics of AIS in patients taking OAC, especially DOAC are sparse [7,8]. Few comparative small studies looked at size, volume and presence of a large vessel occlusion (LVO) [9,10] in patients taking DOAC versus VKA, with preliminary results in favor of DOAC. However, no laboratory assessment of OAC activity or information on compliance for DOAC was available.…”
Section: Introductionmentioning
confidence: 99%
“…Получены пилотные данные, свидетельствующие, что благоприятный клинический эффект может быть связан с формированием инфаркта мозга меньшего объема [21]. Так, выявлен статистически значимо больший объем инфаркта у больных, не получавших ранее ОАК (14,5 [2,0; 59,8] см 3 ), и в случае недостаточной гипокоагуляции на фоне АВК (24,8 [2,1; 63,0] см 3 ), тогда как при МНО ≥2 объем инфаркта составлял 1,3 [0,3; 13,5] см 3 , а у пациентов, ранее принимавших ПОАК, -2,3 [0,5; 21,0] см 3 .…”
unclassified
“…Более того, Y. Sakamoto и соавт. [21] было показано, что нерациональный прием АВК может чаще сопровождаться окклюзией более крупных внутричерепных артерий не только по сравнению с больными, достигшими целевой гипокоагуляции, но и с пациентами, ранее не получавшими ОАК.…”
unclassified
“…Nevertheless, data on imaging characteristics of AIS in patients taking OAC, especially DOAC are sparse (8,9). Few comparative small studies looked at size, volume and presence of a large vessel occlusion (LVO) (10,11) in patients taking DOAC versus VKA, with preliminary results in favor of DOAC. However, no laboratory assessment of OAC activity or information on compliance for DOAC was available.…”
mentioning
confidence: 99%